23.7k views
0 votes
Simplify the following expression.

Simplify the following expression.-example-1
User Swickblade
by
4.3k points

1 Answer

2 votes

Answer:

The answer is cosx cot²x ⇒ the first answer

Explanation:

∵ cot²x = cos²x/sin²x

∵ secx = 1/cosx

∴ cot²x secx - cosx = (cos²x/sin²x)(1/cosx) - cosx

= (cosx/sin²x) - cosx

Take cosx as a common factor

∴ cosx[(1/sin²x) - 1] ⇒ use L.C.M

∴ cosx[1-sin²x/sin²x]

∵ 1 - sin²x = cos²x

∴ cosx(cos²x/sin²x) = cosx cot²x

User Vikramaditya
by
5.4k points